2012
DOI: 10.1080/08897077.2011.640140
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a “Learner-Driven” Curriculum: An Screening, Brief Intervention, and Referral to Treatment (SBIRT) Interdisciplinary Primary Care Model

Abstract: Although screening, brief intervention, and referral to treatment (SBIRT) has been a popular model to address potential substance abuse issues in primary care, there is a need for innovative approaches for training providers and staff on SBIRT protocols. An interdisciplinary approach to SBIRT training, named ICARE, was implemented at 3 different medical settings. The ICARE team trained 85 employees at an academic family medicine residency center and 37 employees across 2 rural community health care clinics. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 2 publications
0
34
0
1
Order By: Relevance
“…Reported outcomes were typically preliminary, anecdotal, and limited to participants' general satisfaction with the initiative and/or self-reported confidence/ self-efficacy in applying new knowledge and skills (Iles-Shih et al, 2011;Marcus et al, 1999;Mihalynuk et al, 2007;Near & Martin, 2007;Stanton et al, 2012;Storti & Maranjian-Church, 1999;Tanner et al, 2012;Truncali et al, 2012). In several instances, however, more rigorous outcomes were reported.…”
Section: Outcomes Of Various Icae Initiativesmentioning
confidence: 95%
See 4 more Smart Citations
“…Reported outcomes were typically preliminary, anecdotal, and limited to participants' general satisfaction with the initiative and/or self-reported confidence/ self-efficacy in applying new knowledge and skills (Iles-Shih et al, 2011;Marcus et al, 1999;Mihalynuk et al, 2007;Near & Martin, 2007;Stanton et al, 2012;Storti & Maranjian-Church, 1999;Tanner et al, 2012;Truncali et al, 2012). In several instances, however, more rigorous outcomes were reported.…”
Section: Outcomes Of Various Icae Initiativesmentioning
confidence: 95%
“…Most articles contained positive anecdotal reports of general course or satisfaction evaluations; these learners enjoyed working under/with faculty and students from other disciplines and believed that the experience prepared them well for clinical practice and/or community partnerships (Baez et al, 2004;Iles-Shih et al, 2011;Mihalynuk et al, 2007;Near & Martin, 2007;Stanton et al, 2012;Tetrault et al, 2012;Truncali et al, 2012). Wendler and Murdock (2006) reported that participants found training on co-occurring disorders relevant and informative, were equally satisfied with peer-led and expert-led modules, and found the interdisciplinary training process to be particularly salient and enjoyable.…”
Section: Feedback From Learners Faculty Members and Other Professiomentioning
confidence: 97%
See 3 more Smart Citations